2014
DOI: 10.1002/er.3201
|View full text |Cite
|
Sign up to set email alerts
|

An experimental investigation into the effects of zeolites on the formation of methane hydrates

Abstract: SUMMARY Methane hydrate is an ice‐like nonstoichiometric compound that forms when methane reacts with water at high pressures and low temperatures. It has a lot of practical applications such as separation processes, natural gas storage transportation, and carbon dioxide sequestration. Especially, the industrial use of hydrates requires large amounts of gas to be formed quickly into hydrates. Porous media significantly influence the rate of hydrate formation by reducing the chemical barrier, where zeolites are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 20 publications
2
25
1
Order By: Relevance
“…3, at hydrate formation conditions, the amount of gas that gets adsorbed in dry zeolite is very small. However it is reported in literature, that at high temperatures, zeolites show significant gas consumption [68][69][70][71][72][73]. On the other hand, according to our observations, at hydrate formation conditions, the gas consumption in presence of water is significantly higher than that in case of dry zeolite.…”
Section: Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…3, at hydrate formation conditions, the amount of gas that gets adsorbed in dry zeolite is very small. However it is reported in literature, that at high temperatures, zeolites show significant gas consumption [68][69][70][71][72][73]. On the other hand, according to our observations, at hydrate formation conditions, the gas consumption in presence of water is significantly higher than that in case of dry zeolite.…”
Section: Resultscontrasting
confidence: 69%
“…However, the effects of different types of Zeolite: 3A, 5A and 13X on methane hydrate formation have been reported in literature [69][70][71].…”
Section: Introductionmentioning
confidence: 98%
“…This unusual behavior was also reported for natural and synthetic zeolites (5 A and 13X), i. e., hydrate formation is easier in the zeolite solutions . Using different water/zeolites suspension, Kim et al.…”
Section: Methane Hydrate In Confined Spacessupporting
confidence: 61%
“…Zeolites are suitable porous materials due to their high mechanical and thermal stability, large surface areas, and tunable surface chemistry. As far as the authors are aware, few zeolites have been reported as methane hydrate promoters: RHO, 13A, 13X, , 3A, and 5A. , …”
mentioning
confidence: 99%